Zoledronic acid effect on bone of growing rats - Lupión, Patricia Melina (2018)
Zoledronic acid (ZA) is an antiresorptive drug used in children with bone diseases like osteogenesis imperfecta, juvenil osteoporosis, fibrous dysplasia and primary bone tumors. The aim of the present study was to evaluate the effects of ZA dose accumulation on growing bone during different periods of treatment in normal rats. Methods: A 4x2 factorial design was used to study the effect of the dose of ZA (D: 0-2.5-12.5-25 µg Z/kg body weight/s.c. weekly) and the length of treatment (T: 15-30 days) in normal female Sprague Dawley rats. Bone morphometric, histomorphometric, densitometric and biomechanical studies were performed. Results: Femoral length and cross-sectional area were affected by both D and T. A significant interaction between D and T was observed in length with a lower value at higher dose and 30 days of treatment. Growth plate of the tibia showed a decrease in total thickness with D and T. Histomorphometric and connectivity parameters of trabecular bone were significantly increased with D and several parameters were also affected by T. Cortical bone strength was increased only with T. Biomechanical parameters of trabecular bone showed significant interaction with greater effect at higher D and T. Conclusion: Even though a mild negative effect of the highest dose of ZA on linear and appositional growth was observed, the other bone parameters evaluated were improved. A careful risk/benefit analysis would lead us to conclude that the mild deleterious effects of ZA during growth are outweighed by the benefit obtained with treatment.